Gingival crevicular fluid levels of interferon‐γ, but not interleukin‐4 or ‐33 or thymic stromal lymphopoietin, are increased in inflamed sites in patients with periodontal disease. (1st April 2013) - Papathanasiou, E.; Flavia, T.; Griffin, T.; Arguello, E.; Finkelman, M.; Hanley, J.; Theoharides, T. C.
<x xml:space="preserve">Abstract</x> Objective To investigate the hypothesis that levels of interferon (IFN)‐γ and interleukin (IL)‐4, as well as the newer cytokines IL‐33 and thymic stromal lymphopoietin (TSLP), in gingival crevicular fluid (GCF) samples differ from sites of patients at various clinical stages of periodontal disease and controls. Background Periodontal diseases result from the complex interplay between pathogenic bacteria and the host's immune responses. Several inflammatory mediators, such as IFN‐γ and IL‐4, have been detected in GCF samples in patients with periodontitis, but the results are mostly contradicting due to the lack of uniformity and collection of sites and methods of analysis. Material and Methods GCF samples were collected from sites with different clinical characteristics (healthy, gingivitis and periodontitis sites) from periodontally healthy ( n = 14), plaque‐induced gingivitis (n = 17) and chronic periodontitis (n = 11) subjects. The GCF samples were analyzed for the frequency of detection and levels of IFN‐γ, IL‐4, IL‐33 and TSLP using a multiplex bead immunoassay. Results Inflamed sites in both patients with plaque‐induced gingivitis and chronic periodontitis showed statistically significantly higher volume of GCF compared to non‐inflamed sites in all patients. IFN‐γ could be detected in about 50–70% of the samples analyzed and at significantly higher levels in sites with periodontitis compared to healthy sites in patients with chronic periodontitis (p = 0.035). We also show a statistically significant decrease of IFN‐? in healthy sites of patients with chronic periodontitis as compared to gingivitis sites in patients with plaque‐induced gingivitis (p = 0.047). Only some of the GCF samples showed detectable levels for IL‐4 and TSLP, while IL‐33 was below the detection level in all samples collected. Conclusions These results suggest that IFN‐γ levels in GCF depend on the clinical stage of the site and not on the disease stage of the patient, but need to be expanded to a greater number of subjects and additional analysis of corresponding gingival tissue biopsies for cytokine gene expression.